Immune thrombocytopenic purpura secondary to tuberculosis - Bharadwaj, Rishab; Munirathnam, Deenadayalan; Sivabalan, Somu (International Journal of Contemporary Pediatrics, 2018)
Immune thrombocytopenic purpura (ITP) is a clinical syndrome characterized by reduced number of circulating platelets. The cause of ITP remains unknown in most cases, although it can be triggered by a viral infection or other immune trigger. Although tuberculosis is associated with a wide range of hematological manifestations, ITP secondary to tuberculosis is a very rare manifestation, especially in children. We describe an 11-year-old female child who presented with skin and mucosal bleeds, thrombocytopenia and chronic submandibular lymphadenitis. Blood and bone marrow investigations were suggestive of ITP. She received IVIg, but response was unsatisfactory, hence she was started on steroids. Concurrently, GeneXpert of lymph node biopsy was positive for tuberculosis. A diagnosis of ITP secondary to tuberculous lymphadenitis was made. She received 6 months of anti-tuberculosis therapy. Steroids were tapered and stopped within 2 months. She responded well with restoration of normal platelet counts and regression of lymphadenopathy. Tuberculosis should be considered as one of the secondary causes of ITP, especially in highly endemic countries.